Silicon acoustoelectronics with thin film lithium niobate. (23rd November 2018) - Bhaskar, Umesh Kumar; Bhave, Sunil Ashok; Weinstein, Dana
Abstract: We report on the acoustoelectric (AE) interaction in heterogeneously integrated thin-film lithium niobate on standard resistivity and high resistivity silicon substrates (LNOSs). The monolithic LNOS platform delivers acoustic waves with a large electromechanical coupling coefficient ( K 2 ) and draws on standard metal-oxide semiconductor field effect techniques to maximise AE interaction by impedance matching the acoustic wave with the semiconductor carriers. Preliminary results are obtained on AE attenuation (4 dB cm −1 ) and AE gain (6 dB cm −1 ). With further improvement of the LN/Si interface, the LNOS platform can be expected to give rise to an era of non-reciprocal silicon acoustoelectronics.